THE SWIMMING OF (D)EFFICIENT BODIES: A PROPOSAL FOR SCHOLASTIC PHYSICAL EDUCATION (Fiep Bulletin - online, 2011)
Qualitative research aiming to adapt (dis)abled students in physical education classes, identifying different senses in activities that compose this imaginary. Selection, analysis of context and routine observations, tried to explain by teachers and students complicity how a apparent disability metamorphoses covering itself again in expressions, encode signals, established in different languages. We propose adaptations in swimming, moment when especial people can achieve the dreamed inclusion. Impossibility was replaced by the space occupied by the disable body, movement flew, languages updated body senses. When giving a new meaning to activities they surpass rules, strict techniques, allowing the bodies to achieve efficiency.
Keywords: physical education; inclusion; (dis)abled bodies